Maximizing an Opportunity for Practice in Realizing Students’ Writing Publication through Thematic Progression Models - Muhamad Zayyinul Muttaqin (ELITE JOURNAL, 2021)
The competence of organizing a highly constructed writing for the students’ publication is academically required. Thus, the students are intended to familiarize with various styles to practice. The thematic progression in this case enables to create a meaningful text as it services numerous techniques to accomplish coherence and cohesion. To accommodate them, this researcher aims to guide as well as facilitate them with manual model: the thematic progression. The virtual coaching was done in two sections: 1) The orientation of essential publication for university level through thematic progression models, and 2) The independent construction of the manuscript. The participants were gained from eight semester in majoring English Education Department of UIN Walisongo Semarang in Academic Years 2019/2020. The findings qualitatively reported that the most students increasingly showed some advances in organizing texts by realizing thematic progression technique.